The effect of hypnosis on pain relief due to injection of dental infiltration anesthesia - Soma Arabzade Moghadam; Fayegh Yousefi; Sahand Saad (Wiley, 2021)
Abstract Background and objective Dental patients often experience the fear of pain induced by injectable anesthesia. This study aimed to investigate the impact of hypnosis on relieving the pain of injected dental infiltration anesthesia. Materials and methods This single‐blind clinical trial was conducted on 32 healthy volunteers to assess the pain perception in mucosal injection. The visual analog scale was applied for the measurement of one‐sided pain intensity in the maxilla without hypnosis. When hypnosis was implemented, the same procedure was performed on the other side of the maxilla reversely within one session. Results Hypnosis implementation significantly decreased the intensity of the perceived pain before anesthesia injection (p = 0.05). Conclusion Hypnosis before the injection of dental infiltration anesthesia could decrease the pain intensity caused by the injection. Therefore, hypnosis therapy is recommended as an effective approach to pain control for anesthesia injection.